Glutamate-evoked jaw muscle pain as a model of persistent myofascial TMD pain? - Castrillon, Eduardo E.; Cairns, Brian E.; Ernberg, Malin; Wang, Kelun; Sessle, Barry; Arendt-Nielsen, Lars; Svensson, Peter (Archives of oral biology, 2008)
Compare pain-related measures and psychosocial variables between glutamate-evoked jaw muscle pain in healthy subjects (HS) and patients with persistent myofascial temporomandibular disorder (TMD) pain. Forty-seven female HS and 10 female patients with persistent myofascial TMD pain participated. The HS received an injection of glutamate into the masseter muscle to model persistent myofascial TMD pain. Participants filled out a coping strategies questionnaire (CSQ), the symptom checklist 90 (SCL-90) and McGill pain questionnaire (MPQ). Pain intensity was assessed on an electronic visual analogue scale (VAS). Pain-drawing areas, numerical rating scale (NRS) scores of unpleasantness, pressure pain thresholds (PPTs) and pressure pain tolerance (PPTOL) were measured. Unpaired t-tests and correlation tests were used for analyses. The groups were significantly different when comparing the CSQ scores of control, decrease, diverting attention, increase of behavioural activities and somatization. The peak VAS pain, NRS of unpleasantness and MPQ scores were not significantly different between groups, but PPT and PPTOL were significantly lower in the TMD patients. Significant positive correlations were found in the TMD patients between peak VAS pain and CSQ catastrophizing score and SCL-90 somatization. The scores of PPTs and PPTOLs, in patients showed positive correlations with CSQ reinterpreting pain sensations scores and PPTs correlated with CSQ praying/hoping scores. Glutamate-evoked pain responses in HS and persistent myofascial TMD pain have similar sensory-discriminative and affective-unpleasantness components but differ in psychosocial features. This study suggests that experimental designs based on glutamate injection into muscle can provide an appropriate model for elucidating persistent myofascial pain conditions.